New report on the bionomics of Coquillettidia venezuelensis in temporary breeding sites (Diptera: Culicidae) - Jeronimo Alencar (Revista da Sociedade Brasileira de Medicina Tropical, 2011)
INTRODUCTION: Findings of immature forms of Coquillettidia venezuelensis in temporary breeding sites, without the presence of aquatic plants or other submerged plant tissue are reported. METHODS: A systematic scooping technique to collect specimens was used at the breeding site. RESULTS: Immature forms of Coquillettidia venezuelensis, Anopheles rangeli, An. evansae and Culex sp. were collected from areas of the hydroelectric power station of São Salvador, State of Goiás. CONCLUSIONS This is a novel finding relating to the bioecology of Cq. venezuelensis, a species of medical interest that has been found naturally infected with arboviruses, including Oropouche and West Nile virus.